CHARACTERIZATION OF XYLANASE AND CELLULASE FROM EXTREMELY HALOALKALIPHILIC ARCHAEON NATRINEMA SP. SSBJUP-1 ISOLATED FROM LONAR LAKE. - J. U. PATIL,; S. S. BAJEKAL, (International Journal of Pharma and Bio Sciences, 2014)
The extremely halophilic archaeon Natrinema sp. strain SSBJUP-1, which produces extracellular cellulase and xylanase, was isolated from the Lonar Lake situated in Buldhana, Maharashtra. The enzymes were optimally active at pH 9–10 and temperature 40–60 0C and they were most stable up to pH 11 and 16 % of NaCl concentration. The xylanase showed maximum activity at 500C and cellulase at 400C. Xylanase kept excellent activity over a broad range of salt concentration from 12 to 22% with highest activity at 16 % NaCl while Cellulase showed maximum activity at 14% of salt. Unlike xylanase that was stimulated by Cu2+, Mg2+and Ca2+, cellulase activity was reduced when treated with Hg2+and Cu2+ and stimulated by Mg2+and Ca2+. This investigation showed that Natrinema sp. strain SSBJUP-1 is a potential source of xylanase and cellulase and an interesting candidate for application in biotechnological processes.